THE IMPACT OF PRODUCT QUALITY AND PRICE ON CUSTOMER SATISFACTION : A CASE STUDY ANALYZE HOTEL & RESIDENCE IN BANDUNG - WEST JAVA - Muhammad, Farrel Febrian; Supriatna, Supriatna; Ratnawati, Aryanti; Ahmaddien, Iskandar; Sartika, Sri Dewi (PT. Altin Riset Publishing, 2025)
The purpose of this study was to determine the effect of product quality and price on customer satisfaction. This research was conducted at a Hotel & Residence located in the city of Bandung. The number of samples in this study was 97 hotels and residences as respondents with data collection through distributing questionnaires. Methods, this research uses descriptive and associative methods. The data analysis technique used in this study is multiple linear regression. Results and value, based on the results of the analysis show that there is a significant positive effect of product quality variables on customer satisfaction at Hotel & Residence Bandung. There is a positive significant effect on the price variable on customer satisfaction at Hotel & Residence Bandung, for Product Quality and Price simultaneously have a significant effect on Customer Satisfaction with a coefficient of determination of 73.4%.